A foucauldian analysis on the perceptions of the hearing-impaired individuals within the family. - Sin, Jiayi. (2012)
Existing theoretical findings on the study of disability have always been focused on understanding individuals with physical impairments and neglected the area of sensory impairments. This study hopes to fill up this gap by studying the self-perceptions of hearing-impaired individuals within the realm of the family where the family is often thought of as one of the first social institutions in socializing members of society. Studying hearing impairment is important as it hinders communication and ultimately affects socialization with others. A qualitative study is conducted with nine hearing-impaired individuals to find out their understandings of the notions of disability, identity, family and themselves. Postmodern theories are used in the analysis of the perceptions to gain a better understanding of the world through the gaze of the hearing-impaired individuals.